Is the death penalty dying? : European and American perspectives - Sarat, Austin; Martschukat, Jürgen (Cambridge books online., 2011)
"Is the Death Penalty Dying? provides a careful analysis of the historical and political conditions that shaped death penalty practice on both sides of the Atlantic from the end of World War II to the twenty-first century. This book examines and assesses what the United States can learn from the European experience with capital punishment, especially the trajectory of abolition in different European nations. As a comparative sociology and history of the present, the book seeks to illuminate the way death penalty systems and their dissolution work, by means of eleven chapters written by an interdisciplinary group of authors from the United States and Europe. This work will help readers see how close the United States is to ending capital punishment and some of the cultural and institutional barriers that stand in the way of abolition"--Provided by publisher